2007
DOI: 10.1155/2007/43424
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cu(II)-ACC Complexes and Conversion of the Bound ACC into Ethylene in the Presence of Hydrogen Peroxide. Detection of a Brown Intermediate at Low Temperature

Abstract: Two copper(II)-ACC complexes were prepared and characterized: [Cu(bpy)(ACC)(H2O)]⋅ CO4 (1) and [Cu(ACC)2]3 ⋅ 4H2O (2). Their crystallographic structures are described and analyzed. Spectroscopic characterizations (UV-visible and EPR) confirm that the structure is maintained in solution. These complexes are able to produce ethylene in the presence of hydrogen peroxide in an “ACC Oxidase-like” reaction in water and in methanol. The conversion of ACC into ethylene depends on the amount of base, and, in methanol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…EDTA also reduced the emission of ET, probably by removing metals that participate in ET biosynthesis throughout Fenton‐type reactions involving 1‐aminocyclopropane‐1‐carboxylic acid (ACC), H 2 O 2 and Cu(II) (Ghattas et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…EDTA also reduced the emission of ET, probably by removing metals that participate in ET biosynthesis throughout Fenton‐type reactions involving 1‐aminocyclopropane‐1‐carboxylic acid (ACC), H 2 O 2 and Cu(II) (Ghattas et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The role played by ROS in the development of epinasty is validated through analysis of carbonyl content in wild-type and xdh Arabidopsis plants treated with 2,4-D, and the protective role of EDTA that prevents protein oxidation. EDTA also reduced the emission of ET, probably by removing metals that participate in ET biosynthesis throughout Fenton-type reactions involving 1-aminocyclopropane-1-carboxylic acid (ACC), H 2 O 2 and Cu(II) (Ghattas et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several years ago, we have reported on a series of structurally characterized Cu(II)-ACC complexes using aminopyridine-type ligands in which ACC is coordinated on the Cu(II) ion in a bidentate manner [20], [21], [22]. These complexes are able to oxidize the bound ACC into ethylene in the presence of hydrogen peroxide.…”
Section: Scheme 2 Examples Of Metal-acc Bioinspired Model Complexes Of Accomentioning
confidence: 99%
“…Indeed, we have observed, using EPR spectroscopy and upon addition of increasing amount of ascorbate, that the Cu(II)reconstituted ACCOs were very difficult to reduce using ascorbate, the co-substrate of ACCO in activity assays. We have previously reported that simple copper-ACC complexes (Scheme 2) were able to produce ethylene from the bound ACC moiety when reacted with hydrogen peroxide, a two electron reduced form of dioxygen [20,22,23]. For this reason, ethylene production mediated by ACCO-Cu enzymes was also evaluated using a peroxide-shunt assay.…”
mentioning
confidence: 99%